Exploring demography and sociological factors underlying decisions to join gangs among Indians - Shankar Durairaja; Geshina Ayu Mat Saat; Mohammad Rahim Kamaluddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
In general, gang can be described as a group of friends with identifiable leadership with certain internal organization that engage in various illegal activities such as crimes and drug trafficking. Although voluminous studies have been conducted in the West regarding gangs and gangsterism but very few studies were actually explored this issue in Malaysia. With this in mind, this study sought to provide some evidence for reasons behind decisions to join gangs as there is a lack of local qualitative research on the phenomenon of gangsterism. This lack is largely due to the vulnerability of people coming forward to share their experiences. The specific aim of this study was to explore demography and sociological factors behind gangsterism among Malaysian Indians. This study utilised a qualitative research design (semistructured interview) based on the inductive approach. Ex-gangsters and police personnel were interviewed individually. Thematic analysis was used to extract main themes and sub-themes. Three demography factors were identified: age, gender, and educational level. Four sociological factors were generated: poor parenting style, family members who were also gangsters, gang culture in the neighborhood, and financial difficulties. Two new factors emerged from the informants: social power and to experience gangster lifestyles. The outcome of this research is useful for proactive crime prevention in the form of evidence-based knowledge about demography and sociological factors behind gangsterism. This paper also briefly discussed intervention, prevention, and suppression strategies that can be used to curb this gangsterism issue effectively.